Peripartum cardiomyopathy: an overview - Wan Ahmad, Wan Azman; Kamar, Haizal Haron (Faculty of Medicine, University of Malaya, 2005)
Peripartum cardiomyopathy (PPCM) is a life-threatening cardio-myopathy of an unknown cause that occurs in the peripartum period in previously health women and this article discusses the challenges that lie in diagnosing and managing this rare yet lethal disease.